Pengaruh Integritas Dan Motivasi Kerja Terhadap Produktivitas Pegawai Dinas Perhubungan Kota Padang - Ardaimon, Asrimeidari (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This study aims to determine the effect of integrity and work motivation on the productivity of Padang City Transportation Department employees. This research was conducted because of the finding of problems related to the lack of employee awareness of the importance of increasing integrity and motivation to increase work productivity. The type of research in this study is quantitative using statistical analysis. The population of this study were 179 employees at the Padang City Transportation Service, while the sample in this study was 169 respondents. The data collection technique in this study used a questionnaire with a Likert scale model. The analysis in this study uses multiple linear regression test. The results of the study indicate that integrity and work motivation have an influence on the work productivity of employees at the Padang City Transportation Service